Pengaruh Solvabilitas, Likuiditas dan Aktivitas Terhadap Profitabilitas Perusahaan Jasa Sektor Infrastruktur, Utilitas dan Transportasi Yang Terdaftar di BEI - Samsul Bahari; Dedi Hariyanto; Heni Safitri (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of solvency by using Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), liquidity by using Current Ratio (CR) and Cash Ratio (CHR) and activities by using Total Assets Turn Over (TATO) and Working Capital Turnover (WCT) on Profitability by using Return on Assets (ROA) on service companies in the infrastructure, utility and transportation sectors listed on the Indonesia Stock Exchange (IDX). This type of research uses quantitative descriptive method. Data collection techniques used in this study are documentation techniques. The analysis technique used is normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, linearity test, multiple regression analysis, analysis of multiple correlation coefficients (R), analysis of coefficient of determination (R2), simultaneous influence test (f test) and partial influence test (t test). The result of the multiple correlation coefficient R of 0.722 means that the variables DER, DAR, CR, CHR, TATO and WCT have a strong relationship to ROA. The results of the coefficient of determination (R2) obtained the results of the six independent variables DER, DAR, CR, CHR, TATO and WCT of 0.419. This means that the influence of DER, DAR, CR, CHR, TATO and WCT is 41.9% on ROA, the remaining 58.1% is explained by other variables not included in the research variable. The result of simultaneous influence test (test f) shows that the six independent variables, namely DER, DAR, CR, CHR, TATO and WCT together have a significant influence on ROA, as evidenced by the calculated F value of 5.087 and F table of 2.43 and has a sig value of 0.001 smaller than 0.05. While the results of the partial effect test (t test) shows that the Debt to Asset Ratio (DAR) variable has a significant negative effect on the variable Return on Assets (ROA), while the Cash Ratio (CHR) and Total Assets Turn Over (TATO) variables have a positive effect significant to the variable Return on Assets (ROA). The Debt to Equity Ratio (DER), Current Ratio (CR) and Working Capital Turnover (WCT) variables do not have a significant effect on the Return on Assets (ROA) variable.